Eko-Eskatologi dalam Mitos dan Tradisi Pante: Refleksi Teologis atas Relasi Manusia dan Alam pada Masyarakat Manggarai NTT - Felix Riondi Sugar; Anjelinus Sandri; Marselinus Langgor; Adelberto Wili Boko; Iluminata Fatreimin Adur; Antonius M. A. Wangga; Melkior R. S. Doa (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
This study examines the eco-eschatological dimensions embedded in the myths and traditions of pante among the Manggarai people of East Nusa Tenggara, Indonesia. The pante tradition is not merely understood as an economic activity involving the tapping and processing of palm sap, but also as a cultural practice that embodies ecological, spiritual, social, and ethical values. Through this tradition, the Manggarai people maintain a harmonious relationship with nature and recognize their responsibility toward the environment as part of a sacred cosmic order. This study employs a qualitative approach based on literature review and hermeneutical-theological analysis to explore the symbolic meanings and theological implications of the pante myth. The findings reveal that the pante myth reflects the Manggarai people’s cosmological worldview, in which nature is regarded as a living and sacred reality that must be respected and protected. Furthermore, the tradition promotes an ethic of sustainability that discourages excessive exploitation of natural resources and encourages balance between human needs and environmental preservation. From an eco-eschatological perspective, the pante tradition represents a vision of hope for the restoration of relationships among humans, nature, and God, anticipating the fulfillment of the “new heaven and new earth.” Therefore, this study affirms that Manggarai local wisdom provides a valuable contribution to the development of contextual, ecological, and sustainable theology in contemporary society.